PENERAPAN STRATEGI ORGANISASI, E-BUSINESS, DAN E-COMMERCE DISTRIBUTOR PT NATURAL NUSANTARA - Mei Nurlinda (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Today's era is increasingly advanced and developing not only from information but also business and trade. In a company that is engaged in both services and sales, it certainly has goals, the goals of the company will become the basis for the company's performance so that the company will progress and develop. This progress must of course be accompanied by a good strategy so that the company's goals can be achieved optimally. E-business and E-commerce have their own meanings, but these 2 things have one thing in common, that is, all of their activities use technology. Usually companies implement either e-business or e-commerce. However, PT Natural Nusantara applies E-business and e-commerce in its operational activities In this article the author identifies e-business and e-commerce that are applied to PT Natural Nusantara and describes them in a paper.